2005
DOI: 10.1111/j.1572-0241.2005.40310.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic Liver Abscess with a Focus on Klebsiella pneumoniae as a Primary Pathogen: An Emerging Disease with Unique Clinical Characteristics

Abstract: These data suggest that KLA may represent an emerging disease in Western countries, such as the United States. The diagnosis of K. pneumoniae should be considered in all cases of liver abscess, and appropriate antibiotic therapy and a diagnostic work-up for metastatic complications should be employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
283
5
15

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(317 citation statements)
references
References 42 publications
14
283
5
15
Order By: Relevance
“…The results contrast with numerous series that reported progressive increase of K. pneumoniae over E. coli as primary pathogen causing PLA, especially in patients with diabetes mellitus. 1,5,[12][13][14][15][16][17] The isolation of MDRB was slightly higher as compared to other reports 17 and could be explained by the notable presence of patients with chronic disease and history of prolonged hospitalizations. A 75% of MDRB were isolated in transplant recipients or patients with NBIPLA with active oncologic disease.…”
Section: Discussionmentioning
confidence: 63%
“…The results contrast with numerous series that reported progressive increase of K. pneumoniae over E. coli as primary pathogen causing PLA, especially in patients with diabetes mellitus. 1,5,[12][13][14][15][16][17] The isolation of MDRB was slightly higher as compared to other reports 17 and could be explained by the notable presence of patients with chronic disease and history of prolonged hospitalizations. A 75% of MDRB were isolated in transplant recipients or patients with NBIPLA with active oncologic disease.…”
Section: Discussionmentioning
confidence: 63%
“…[1][2][3][4] Its emergence in western countries has also been reported. [5][6][7] Previous studies in Taiwan, Singapore and Korea found a high prevalence of the capsular polysaccharide (CPS) K antigen serotypes K1 (54.5-63.4%) and K2 (5-21.2%) of K. pneumoniae in liver abscess isolates. 1,[8][9][10] Apart from the capsular serotypes, other virulence determinants have also been reported for K. pneumoniae liver abscesses, including the presence of hypermucoviscosity, aerobactin, magA (mucoviscosity-associated gene A), rmpA (regulator of mucoid phenotype), kfu (responsible for an iron uptake system) and allS (associated with allantoin metabolism) genes.…”
mentioning
confidence: 99%
“…The incidence of K. pneumoniae infection increases in immunocompromised conditions, such as diabetes mellitus, alcoholism, malignancy, hepatobiliary disease, chronic obstructive pulmonary disease, glucocorticoid therapy and renal failure [6][7][8][9][10][11][12][13][14]. In our case, the In a few cases, K. pneumoniae liver abscess has been associated with metastatic infection at other sites [7,8,[10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 97%